Effect of infrared Radiation on two storedproduct insects and barley grain Germination on grain - A. Bunian, Muna . (Al-Qadisiyah Journal of Pure Science, 2017)
This study handles the effect of the infrared radiation (IR) from a red incandescent bulb at three exposure distances [ 6 , 8.5 , 10 cm] and five exposure periods[2,3,4,5,6 and minutes ]at the larval , pupal and adult stages of confused flour beetle Tribolium confusum and rusted flour beeteTribolium castanum in addition to the effect of the IR on germinations grain and barley . The effect of IR on each insect species increases with the decrease of the exposure distance and increases as well with the increase of The exposure period. The 6cm exposure distance at 6 exposure periodskills all the stage of the two species. Exposure distances and periods show significant difference on percentage and speed of grain germination of wheat and barley.